Fire Prevention System Using RGB Algorithm - Amirathul Athirah Abdul Rahman; Norharyati Harum; Erman Hamid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Most of the fire prevention system use smoke and heat sensors to detect the fire, leads to late action to stop the fire and cause a large damage. To avoid the problem, a fire prevention system that utilizes the RGB algorithm for early fire detection has been developed. By employing RGB algorithm and real-time monitoring, the system aims to enhance fire safety in various environments. The system consists of high-resolution cameras strategically placed in the monitored area. These cameras capture real-time video that are processed using the RGB algorithm. The algorithm analyses the video to identify patterns indicative of a fire outbreak, such as intense red and orange colours, and changes in brightness. Once a potential fire hazard is detected, the system triggers immediate alerts to relevant stakeholders through Telegram notifications, and audible alarms. To complement early detection, the system incorporates preventive measures such as automatic sprinkler systems, which can be activated manually or automatically. Overall, the fire prevention system leveraging the RGB algorithm offers early fire detection, real-time monitoring, and seamless integration with existing fire safety infrastructure. By combining these features, the system has the potential to significantly enhance fire safety in various environments, protecting lives and property.